High-precision indoor fast positioning algorithm based on carrier phase - Shaoshuai FAN; Zhiqiang RONG; Hui TIAN; Lihua LI (Tongxin xuebao, 2022)
In order to improve the positioning accuracy and the speed of position solution in indoor wireless environment, a high-precision indoor fast positioning algorithm based on carrier phase was proposed.By introducing the reference terminal, the influence of clock error between devices on the accuracy of the positioning algorithm was completely eliminated by using the double difference between the carrier phase measurements of the terminal to be positioned and the reference terminal.Taking advantage of the invariability of integer ambiguity during the phase-locked loop lock-off, an iterative integer ambiguity resolution algorithm based on multi-time point measurement data was designed, and the fast integer ambiguity resolution was realized.After the integer ambiguity was solved, the terminal to be located could be located with high precision by using accurate carrier phase difference measurement.The simulation results show that the positioning algorithm proposed can completely overcome the influence of clock error on positioning performance, and can achieve centimeter-level positioning accuracy at very few sampling time points.